Epe1 contributes to activation of AMPK by promoting phosphorylation of AMPK alpha subunit, Ssp2 - Yongyi Chen (Nature Portfolio, 2017)
Abstract AMP-activated protein kinase (AMPK) is a pivotal cellular energy sensor. It is activated by stresses that cause depletion of energy and initiates adaptive responses by regulating metabolism balance. AMPK forms αβγ heterotrimer. In fission yeast, activation of AMPK mainly depends on the phosphorylation of AMPKα subunit Ssp2 at Thr189 by upstream kinase Ssp1. However, not much is known about the regulation of this process. In this study, we identified Epe1 as a novel positive regulator of AMPK. Epe1, a jmjC-domain-containing protein, is best-known as a negative regulator of heterochromatin spreading. Although the novel role of Epe1 in regulation of AMPK relies on predicted iron- and 2-oxyglutarate-binding residues inside jmjC domain, it seems to be irrelevant to inhibition of heterochromatin spreading. Epe1 is associated with Ssp2 directly and promotes phosphorylation of Ssp2 upon various environmental stresses, including low-glucose, high-sodium, high-pH and oxidative conditions. Similar to Epe1, Jmj1 and Msc1 also contribute to phosphorylation of Ssp2. Deletion of epe1 + impairs downstream events following phosphorylation of Ssp2, including nuclear translocation of Ssp2, sexual differentiation and inhibition of fatty acid synthesis. Our study reveals a novel way in which a jmjC-domain-containing protein regulates adaptive response by directly binding to a principal sensor.